2011
DOI: 10.1088/0029-5515/51/7/073023
|View full text |Cite
|
Sign up to set email alerts
|

Latest investigations on fluctuations, ELM filaments and turbulent transport in the SOL of ASDEX Upgrade

Abstract: Abstract. This paper presents turbulence investigations in the scrape off layer (SOL) of ASDEX Upgrade in Ohmic, L-mode and H-mode discharges using electrostatic and electromagnetic probes. Detailed studies are performed on small scale turbulence and on ELM filaments. Simultaneous measurements of floating and plasma potential fluctuations revealed significant differences between these quantities. Large errors can occur when the electric field is extracted from floating potential measurements, even in Ohmic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 46 publications
8
75
0
Order By: Relevance
“…Comparison of E r from Doppler reflectometry with E r obtained with a heavy ion beam probe at TJ-II showed good agreement [35]. Furthermore, comparisons with E r from spectroscopy in W7-AS [40] and with E r from a Ball pen probe in ASDEX Upgrade [45] have also shown that v ph ≪ v E×B holds. In DIII-D, E r from beam emission spectroscopy and charge exchange recombination spectroscopy measurements also confirm the above statement [9].…”
Section: Figmentioning
confidence: 67%
“…Comparison of E r from Doppler reflectometry with E r obtained with a heavy ion beam probe at TJ-II showed good agreement [35]. Furthermore, comparisons with E r from spectroscopy in W7-AS [40] and with E r from a Ball pen probe in ASDEX Upgrade [45] have also shown that v ph ≪ v E×B holds. In DIII-D, E r from beam emission spectroscopy and charge exchange recombination spectroscopy measurements also confirm the above statement [9].…”
Section: Figmentioning
confidence: 67%
“…. Surprisingly, the net radial efflux of particles during a type II ELMing period is larger than that during type I ELMs (see also reference [19]). Some of the enhanced flux in the type II ELMs is due to the larger J SAT signals in between the filaments but the effect of this is estimated to be less than 10 % of the total flux.…”
Section: The Spatial and Temporal Structure Of Type II Elms On Asdex mentioning
confidence: 99%
“…The CPS of the Li-BES at higher frequencies f > 30 kHz remains at the same level, whereas the spectrum of the ion saturation data continuously decreases. The image size of the optics is 6 mm × 12 mm, whereas the probe has a diameter of < 2 mm [34]. Therefore, structures with a perpendicular wavenumber k ⊥ larger than the corresponding wavenumber of the observation volume cannot be resolved, because of ω = v ⊥ k ⊥ depending on k ⊥ and the perpendicular velocity v ⊥ .…”
Section: Li-bes Spectra In Comparison To Other Diagnosticsmentioning
confidence: 99%